Integrating Interprofessional Education and Simulation in Community Health: Evaluation of a Practice-based Student Clinic - Taylor, Jane; Burley, Mollie; Nestel, Debra (International Journal of Practice-based Learning in Health and Social Care, 2015)
There is an increasing need to deliver high quality integrated health services which address expanding numbers and increasing complexity of clients attending for health and social care. Despite demands to educate a future health care workforce with the capacity to deliver integrated team based services to meet these needs there is little in the literature about interprofessional education (IPE) in community health. We developed and evaluated a unique pilot simulated interprofessional student supervised clinic, integrated into the practice in a rural community health service. Pairs of students from two different disciplines interviewed a volunteer simulated client (SC) representing a real client case, and prepared a health care plan for the SC. Thematic analysis revealed overlap between the two groups. Both groups saw it as a positive experience. Students’ responses to a questionnaire revealed they increased their client focus, interacted more with the other disciplines and found it highly realistic and authentic. Analysis of phone interviews with SCs confirmed the realism. SCs also saw it as supporting students’ learning for the real world, and acknowledged the importance of support for themselves. This project confirms the perceived value of practice-based IPE with SCs from the perspectives of students and SCs in social care.